HARMONIZATION OF CROSS-BORDER CARTEL IN THE ASEAN ECONOMIC COMMUNITY - Irena Sasty Audila; Ria Setyawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Association of Southeast Asian Nations (ASEAN) is an intergovernmental organization that has agreed to form the ASEAN Economic Community (AEC). The AEC will transform ASEAN into a single market and production base. Focus on the free trade sector for goods, services, investment, skilled labor, and capital flows. Cartel practices can grow and develop in this situation, where a group of business actors from two or more countries can control the price and quantity of goods or services. The purpose of this study is to find out and understand ASEAN cross-border cartel control, as well as provide an overview of how ASEAN member countries harmonize the competition law products relating to cross-border cartels. The type of research method is normative, which is the legal research to find the truth of coherence whether the problem discussed is under the norms, principles, and the rule of law. Applied analysis is carried out to find solutions to the problems posed and related to comparative analysis to make comparisons. The research results show that ASEAN does not currently have binding laws regarding cross-border cartels. Each ASEAN member country has its business competition law. When cross-border cartel practices in ASEAN occur, effective harmonization of cross-border cartel regulation is needed to oversee anti-competitive activities in the ASEAN region